Arrangement of Tourism Area Management to Achieve the Welfare of Indigenous Peoples of Papua - Sari, Liani (Faculty of Law Cenderawasih University, 2017)
The purpose of this research is to know and understand the management of the tourism area to realize the welfare of the existing indigenous people. The results of the research indicate that the regulation of tourism area management to realize the welfare of the existing indigenous peoples in Jayapura city and district is only managed by indigenous peoples, so that the government and entrepreneurs are not involved in tourism management. This is not in accordance with tourism arrangements where in the management of tourism areas must be managed by indigenous peoples, government and business actors (entrepreneurs).Â